Three-Dimensional Isotropic Fat-Suppressed Proton Density-Weighted MRI at 3 Tesla Using a T/R-Coil Can Replace Multiple Plane Two-Dimensional Sequences in Knee Imaging - Homsi, R.; Gieseke, J.; Luetkens, J. A.; Kupczyk, P.; Maedler, B.; Kukuk, G. M.; Träber, F.; Agha, B.; Rauch, M.; Rajakaruna, N.; Willinek, W.; Schild, H. H.; Hadizadeh, D. R. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: To evaluate whether a 3 D proton density-weighted fat-suppressed sequence (PDwFS) of the knee is able to replace multiplanar 2D-PDwFS.Materials and Methods: 52 patients (26 men, mean age: 41.9 ± 14.5years) underwent magnetic resonance imaging (MRI) of the knee at 3.0 Tesla using a T/R-coil. The imaging protocol included 3 planes of 2D-PDwFS (acquisition time (AT): 6:40 min; voxel sizes: 0.40 – 0.63 × 0.44 – 0.89 × 3mm³) and a 3D-PDwFS (AT: 6:31 min; voxel size: 0.63 × 0.68 × 0.63mm³). Homogeneity of fat suppression (HFS), artifacts, and image sharpness (IS) were evaluated on a 5-point scale (5[excellent] – 1[non-diagnostic]). The sum served as a measure for the overall image quality (OIQ). Contrast ratios (CR) compared to popliteal muscle were calculated for the meniscus (MEN), anterior (ACL) and posterior cruciate ligaments (PCL). In 13 patients who underwent arthroscopic knee surgery, two radiologists evaluated the presence of meniscal, ligamental and cartilage lesions to estimate the sensitivity and specificity of lesion detection.Results: The CR was higher in the ACL, PCL and MEN in 3D- PDwFS compared to 2D-PDwFS (p < 0.01 for ACL and PCL; p = 0.07 for MEN). Compared to 2 D images, the OIQ was rated higher in 3D-PDwFS images (p < 0.01) due to fewer artifacts and HFS despite the lower IS (p < 0.01). The sensitivity and specificity of lesion detection in 3D- and 2D-PDwFS were similar.Conclusion: Compared to standard multiplanar 2D-PDwFS knee imaging, isotropic high spatial resolution 3D-PDwFS of the knee at 3.0 T can be acquired with high image quality in a reasonable scan time. Multiplanar reformations in arbitrary planes may serve as an additional benefit of 3D-PDwFS.Key Points:• 3D-PDwFS of the knee is acquired with high image quality• 3D-PDwFS can be achieved in only one measurement with a reasonable scan time• 3D-PDwFS with the advantage of multiplanar reformation may replace 2D-PD-weighted knee MRICitation Format:• Homsi R, Gieseke J, Luetkens JA et al. Three-Dimensional Isotropic Fat-Suppressed Proton Density-Weighted MRI at 3 Tesla Using a T/R-Coil Can Replace Multiple Plane Two-Dimensional Sequences in Knee Imaging. Fortschr Röntgenstr 2016; 188: 949 – 956
Keywords: knee; 3 D; MRI; multiplanar reformation; proton density-weighted